Splenic anaemia: with special reference to hepatolienal fibrosis - McMichael, John (The University of Edinburgh, 1933)
Modern Medicine can never cease to honour the spirit of William Harvey who dared to challenge classical doctrine in quest of the ultimate truth. His lesson in critical reinvestigation of the bases of an unsatisfactory hypothesis may still be learned with advantage. Studies in the group of diseases known as "splenic anaemia" have too long been haunted by the spectre of " Banti's Disease ", an ill-defined conception shrouded in an obscurity which has proved an insurmountable barrier.

The last account given by Banti of his disease was based on a study of 50 personal cases. Almost without exception, the writings on splenic anaemia since Banti's work became generally known, have been confused by attempts to correlate the findings with Banti's descriptions. This method of approach invariably led into a blind alley, owing to the rigid and highly individualistic views held by Banti. On the basis of pathological material from 89 cases of splenic anaemia, the writer has ventured to break away from this classical method of approach. The term "splenic anaemia" is used in its original historical sense as a generic term for a group of diseases. The commonest member of this group is hepatolienal fibrosis. Banti's disease is relegated to a minor position as one of the syndromes which may occur among the varying clinical and pathological manifestations of this disease. This broader outlook has led to a new conception of the pathogenesis of hepatolienal fibrosis, which, if substantiated, may have its repercussions on the rationale of treatment. The value of splenectomy has been called in question.

As the primary object of the work was the elucidation of the pathology of the various diseases classed as "splenic anaemia", little new ground has been broken in the study of the clinical features. Nevertheless the mass of material has yielded data, which, though meagre on some points, may be of some value as a starting place for the further study of the manifold inter-relations of the liver, spleen and haematopoietic system.